Anti-Leishmanial Activity of the Leaves of Hyoscyam using Extraction Promastigotes of Leismania Major In-Vitro - Mahmoodreza Behravan (Journal of Global Pharma Technology, 2017)
Background and aim Protozoan of Leishmaniasppisaagent of disease of cetaceous leishmaniasis (or tropical sore) and kala-azarworldwide. Due to the prevalence of leishmaniasisin different parts of the world and in Iran, and considering that pentavalent antimony compounds for the treatment of disease has severalside effects, the use of medicinal plants is emphasized. By increasing drug resistance in the treatment of diseases especially parasitic diseases, as well as the existence of the side effects of chemical compounds, the use of herbal medicines has been increased in the treatment of parasitic diseases worldwide. Method and Material In this experimental study, first the alcoholic and hydro extract of the fresh, dried and powdered plant was provided by the method of distillation with water vapor and then various concentrations of 0.25, 0.5, 1, 2, 4 mg/ml of the extract were added to the culture environment containing promastigotes of Leis mania major. After adding extract at 6, 12, 24, 48 and 72 hours the number of live parasites was evaluated and numeratedby MTT colorimetric method and using the Neuberger slide. Results The results of the research showed there isa significant reduction in the number of parasites of Leishmaniain terms of time; that has been created in response to extract Hyoscyamusniger. So in investigating the effect of plant extract of Hyoscyamusnigeronpromastigotes of Leis mania major in concentration 4theparasite existing in vitro was almost equal to zero. All examined concentrations (0.25, 0.5, 1, 2, 4 mg/ml) of this extract have caused to reduce the number of parasites of leis mania. Conclusion This extract has had very favorable effect on extract promastigotesofLeishmania major and could destroy almost all parasites present in the culture environment and therefore this plant can be used as the successor of the Glucan time drug in the treatment of leishmaniasisdisease.Keywords: Leishmania major, Hyoscyamusniger, MTT, In-vitro.